2021
DOI: 10.1021/acsami.1c02755
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid Nanoparticles as Antiviral and Anti-inflammatory Agents for COVID-19 Treatment

Abstract: COVID-19 has been diffusely pandemic around the world, characterized by massive morbidity and mortality. One of the remarkable threats associated with mortality may be the uncontrolled inflammatory processes, which were induced by SARS-CoV-2 in infected patients. As there are no specific drugs, exploiting safe and effective treatment strategies is an instant requirement to dwindle viral damage and relieve extreme inflammation simultaneously. Here, highly biocompatible glycyrrhizic acid (GA) nanoparticles (GANP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 44 publications
(80 reference statements)
0
80
0
2
Order By: Relevance
“…In an assimilated SARS-CoV-2-infected mouse model, nanoparticles carrying GA demonstrated therapeutic effects through anti-inflammatory and antioxidant activities [ 37 ]. At the intracellular and circulating levels, GA binds to high-mobility group box 1 protein (HMGB1) to provide robust anti-inflammatory and neuroprotection [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an assimilated SARS-CoV-2-infected mouse model, nanoparticles carrying GA demonstrated therapeutic effects through anti-inflammatory and antioxidant activities [ 37 ]. At the intracellular and circulating levels, GA binds to high-mobility group box 1 protein (HMGB1) to provide robust anti-inflammatory and neuroprotection [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have demonstrated that the GA can be considered as one promising anti-SARS-CoV-2 drug candidate, alone and in combination with other drugs (e.g., chloroquine and tenofovir), to combat the current COVID-19 pandemic [ 19 ]. This is mainly due to the capacity of GA to bind to the angiotensin converting enzyme 2 (ACE2), a SARS-CoV-2 receptor, which can prevent the virus from diffusing out of infected cells and to enter new cells [ 19 , 53 , 54 , 55 ]. In addition, other structurally related saponins with the membrane-perturbating effects, such as escin, platycodin D and saikosaponin, also exhibit strong biological activity against coronavirus [ 19 , 56 , 57 ].…”
Section: Biological Activities Of Saponinsmentioning
confidence: 99%
“…Synthesizing highly biocompatible glycyrrhizic acid NPs demonstrated a significantly enhanced antiviral and anti-inflammatory effects in vitro and in vivo. 152 A typical Indonesian natural product administration culture, called jamu, is commonly practiced to relieve pain and inflammation from acute and chronic disorders. The efficacy and the value of jamu have been improved using various nanotechnology approaches such as nanosuspension, nanoemulsion, nanoencapsulation, and nanofiber fabrication.…”
Section: Nanostructure-based Covid-19 Managementmentioning
confidence: 99%